2020
DOI: 10.3390/w12082150
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Behavior of an Activated Carbon for Bisphenol A Removal in Single and Binary (Bisphenol A—Heavy Metal) Solutions

Abstract: Bisphenol A (BPA) is an extensively produced and consumed chemical in the world. Due to its widespread use, contamination by this pollutant has increased in recent years, reaching a critical environmental point. This work investigates the feasibility of bisphenol A adsorption from industrial wastewater solutions, testing the reduction of bisphenol A in synthetic solutions by a commercial activated carbon, AC-40, in batch mode. Besides, mixtures of bisphenol A and different heavy metal cations were also studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 69 publications
3
15
1
Order By: Relevance
“…As a result, the BPA could not be taken by the adsorbent, thus, reducing the removal efficiency of the adsorbent (Huang and Wang 2018). These results were in accordance to other previous works (Liu et al 2018;Martín-Lara et al 2020). It should be noted that when the BPA concentration was higher than 100 mg•L -1 , the BPA removal (%) was not substantially influenced by the initial BPA concentration.…”
Section: Effect Of Initial Concentration Of Bpa Solutionsupporting
confidence: 91%
“…As a result, the BPA could not be taken by the adsorbent, thus, reducing the removal efficiency of the adsorbent (Huang and Wang 2018). These results were in accordance to other previous works (Liu et al 2018;Martín-Lara et al 2020). It should be noted that when the BPA concentration was higher than 100 mg•L -1 , the BPA removal (%) was not substantially influenced by the initial BPA concentration.…”
Section: Effect Of Initial Concentration Of Bpa Solutionsupporting
confidence: 91%
“…Among them, activated carbon has been used as a typical general adsorbent due to getting at ease, inexpensive, and so on. Many studies on the adsorption of EDCs onto activated carbon have been carried out in terms of especially adsorption kinetics and adsorption isotherm (Toledo et al, 2005;Hohan et al, 2007;Kumar and Namasivayam, 2014;Sudhakar and Srivastava, 2016;Martín-Lara et al, 2020). However, most of these studies have only reported which are the well-established adsorption kinetics models or adsorption isotherms equations agreed well with the experimental results.…”
Section: Introductionmentioning
confidence: 91%
“…is phenomenon promotes the establishment of electrostatic interactions of an attractive nature between the bisphenol A molecules positively charged in solution and the NSST activated carbon whose surface is negatively charged. is is due to the fact that the pH ZPC (6,94) of NSST AC is greater than pH 6 of the analyte solution [45]. Figure 5(b) shows that the quantity of adsorbed pollutant decreases when the mass of carbon increases from 25 to 100 mg. is behavior may be due to the number of adsorption sites, which decreases with the amount of adsorbent [46].…”
Section: Pareto Diagram and Analysis Of Adsorption Response Surfaces ...mentioning
confidence: 96%